Flujo De Trabajo Para El Proceso De Etl Del Portal De Datos Abiertos Bogotá Para Generar Un Formato Más Legible Y Limpio A Través De La Herramienta Databricks (2024)
In this project, the transformation and cleaning of the dataset “Confirmed COVID19 Cases in Bogotá D.C.” from the Bogotá Open Data source are addressed. These processes are guided by the application of capability areas established by DAMADMBOK. The process focuses on applying best practices to improve quality and organization, facilitating analysis and ensuring access to information through the Databricks tool, where the development of a workflow will guide the applicability in the project with ETL processes and the implementation of best practices in data governance. The applicability of this project also extends to the use of the Databricks tool, demonstrating its capacity and scalability in data integration and interoperability processes, as well as in data analysis.